Development of a Management Practice Framework for Social Enterprises: A Conceptual Synthesis - Kolsamon, Sunanta; Suveatwatanakul, Chokechai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This academic article aimed to conceptually synthesize and develop a management practice framework for social enterprises. A review of the literature indicated that although research on social enterprises had increased steadily, most studies primarily focused on social impact, business models, or the role of entrepreneurial ecosystems. In contrast, research explaining internal management mechanisms through which social missions were systematically translated into business operations remained limited. This situation highlighted a gap in the literature regarding management practices that support the long-term sustainability of social enterprises. This study employed a literature review and conceptual synthesis of research related to social enterprises, organizational management, and organizational sustainability in order to develop a systematic conceptual framework. The synthesis resulted in the proposal of a management practice framework for social enterprises consisting of eight key dimensions: 1) clearly defined social mission identity, 2) human resource management in the specific context of social enterprises, 3) developing entrepreneurial competencies in employees, 4) social enterprise innovation, 5) social marketing, 6) entrepreneurial ecosystem management, 7) sharing with competitors, and 8) resilience development. The proposed framework represented a novel contribution to the literature by presenting a practice-oriented management perspective that systematically integrated mission, strategy, operations, and performance measurement. The framework explained mechanisms through which social enterprises generated social impact while maintaining economic sustainability and provided guidance for managerial practice and future research.